Penalties And Liquidated Damages In A Changing World: Rethinking The Common Law Position - Odetola, Oluwadamilola (Journal of Sustainable Development Law and Policy, 2025)
Why did Antonio agree to give Shylock a pound of his flesh in theMerchant of Venice? Why was Shylock unable to get his pound offlesh? Parties to a contract are allowed to determine their obligations butcannot freely determine the consequences of breach in the event of nonperformance. Such is the paradox in the law of obligations. Virtually everymodern contract contains a liquidated damages clause and common lawjurisdictions strive to ensure that such clauses do not offend the ruleagainst penalties. This paper examines the principle of contractual freedomwithin the narrower context of liquidated damages and penalty clauses.It revisits the principles of the law of penalties as expounded in the classiccase of Dunlop Pneumatic Tyre Co. Ltd v. New Garage & Motor Co.Ltd, and considers how well they have fared after a century. In makingthis evaluation, particular attention is paid to English, Australian andNigerian law. There are issues thrown up by the rigid dichotomy betweenliquidated damages and penalties and the extent to which commercialpartners can negotiate around them. As commercial contracts becomemore complex and multi-jurisdictional, clarity, certainty and security oftransactions have become more fundamental to commercial dealings. Thisarticle finds that the dichotomy between penalty and liquidated damageshas not only become irrelevant, it also undermines these fundamentals.Arguments made in favour of the dichotomy are self-defeating andconfusing. Judicial attempts to bring the penalty rule in consonance withcommercial realities also come with problems of their own. Therefore,an abolition of the dichotomy is advocated. This article proposes that inplace of the existing unjustifiable paternalistic approach, all agreed damages should be prima facie valid, subject to clear cases of unequalbargaining power and economic oppression.